Two Facets of Returnees’ Entrepreneurship in Romania: Juxtaposing Business Owners and Self-Employed Return Migrants Within a Multi-Method Research Framework - Croitoru, Alin; Coșciug, Anatolie (Calitatea Vieții, 2021)
This paper contributes to the growing literature on the diversity of return migration by analysing the different types of small-scale entrepreneurship among returnees. Data from an original survey conducted among Romanian returnees and in-depth interviews with returnees in entrepreneurship are combined to reveal distinct profiles of returnee entrepreneurs and to illustrate their specific ways of thinking about entrepreneurship and migration. Currently, Romania is one of the most fertile settings to research intra-European return migration due to its important flows of temporary international migrants. The paper highlights that there are major differences between business owners and self-employed returnees in terms of entrepreneurship. Returnees who are business owners are those who benefited significantly more from migration than non-entrepreneur returnees—in terms of economic savings, human capital accumulation, and enhancement of their stocks of social capital; while returnees in self-employment reveal no significant differences for these migration outcomes compared to non-entrepreneur returnees. The distinction between the two groups of entrepreneurs has certain implications for origin states’ policies oriented towards stimulating return migration through programmes oriented towards returnees’ entrepreneurship.